Broca’s Area as a Pre-articulatory Phonetic Encoder: Gating the Motor Program - Ferpozzi, Valentina; Fornia, Luca; Montagna, Marcella; Siodambro, Chiara; Castellano, Antonella; Borroni, Paola; Riva, Marco; Rossi, Marco; Pessina, Federico; Bello, Lorenzo; Cerri, Gabriella (Frontiers in Human Neuroscience, 2018)
The exact nature of the role of Broca’s area in control of speech and whether it is exerted at the cognitive or at the motor level is still debated. Intraoperative evidence of a lack of motor responses to direct electrical stimulation (DES) of Broca’s area and the observation that its stimulation induces a “speech arrest” without an apparent effect on the ongoing activity of phono-articulatory muscles, raises the argument. Essentially, attribution of direct involvement of Broca’s area in motor control of speech, requires evidence of a functional connection of this area with the phono-articulatory muscles’ motoneurons. With a quantitative approach we investigated, in 20 patients undergoing surgery for brain tumors, whether DES delivered on Broca’s area affects the recruitment of the phono-articulatory muscles’ motor units. The electromyography (EMG) of the muscles active during two speech tasks (object picture naming and counting) was recorded during and in absence of DES on Broca’s area. Offline, the EMG of each muscle was analyzed in frequency (power spectrum, PS) and time domain (root mean square, RMS) and the two conditions compared. Results show that DES on Broca’s area induces an intensity-dependent “speech arrest”. The intensity of DES needed to induce “speech arrest” when applied on Broca’s area was higher when compared to the intensity effective on the neighboring pre-motor/motor cortices. Notably, PS and RMS measured on the EMG recorded during “speech arrest” were superimposable to those recorded at baseline. Partial interruptions of speech were not observed. Speech arrest was an “all-or-none” effect: muscle activation started only by removing DES, as if DES prevented speech onset. The same effect was observed when stimulating directly the subcortical fibers running below Broca’s area.